SOA-based dynamic coordination architecture for IP network management systems - LI Wen-jing; QIU Xue-song (Tongxin xuebao)
The applicable scope and constraints of several dynamic coordination architectures between IP network man-agement systems in the heterogeneity environment were analyzed. A SOA-based architecture for dynamic coordination between IP network management systems was proposed, which combines the peer distribution and integrated manage-ment, realizing the end-to-end dynamic coordination. The architecture conceals the heterogeneity between IP network management systems effectively and has good capability of loose-coupled and dynamic coordination.